Helden und Wir: Neue Beiträge zum Zeitbild der Person - Stekeler, Pirmin (Philosophische Rundschau, 2020)
Heroes and saints are idealized images of people. Reflecting on them is thinking about our times. We can see this at Roger Scruton's new book on Wagner's Parsifal, Michael Hampe's philosophical novel about the strife to step out of the demands of our society, Ulrich Bröckling's sceptical essay on postheroism, which contradicts Dieter Thomä's claim that our democracies need more heroes. The review of the four books is placed under four titles: 1. anointment as a hero - or how Parsifal becomes a saviour; 2. heroes in the void - or how the search for authenticity ends in death; 3. fallen heroes - or how we only blink when we hear about heroism; 4. resurrection of heroes? - or how Superman supports the illusion of democratic heroes.Roger Scruton: Wagner's Parsifal. The Music of Redemption. London 2020: Penguin. 208 S. - Michael Hampe: Die Wildnis. Die Seele. Das Nichts. Über das wirkliche Leben. München 2020. Hanser. 304 S. - Ulrich Bröckling: Postheroische Helden. Ein Zeitbild. Berlin 2020: Suhrkamp. 277 S. - Dieter Thomä: Warum Demokratien Helden brauchen. Plädoyer für einen zeitgemäßen Heroismus. Berlin 2019: Ullstein. 272 S.